(untitled) (Intent Research Scientific Journal, 2023)
This research paper explores the importance of reforestation in preventing desertification. The article reviews the literature on the impact of reforestation on the process of desertification. A methodology based on a comparative analysis of various studies and their results was used. The results of the conducted work confirm that reforestation helps to restore biodiversity, improve soil quality, reduce erosion and carbon dioxide emissions, and create favorable conditions for local residents. A discussion of the research results reveals the benefits of reforestation as well as possible ways to improve it. In conclusion, the results of the study were summarized and recommendations were developed for further study and practical application of forest restoration in the fight against desertification.